Preparation of anorthite ceramic using mining tailings and calcium fluoride sludge. (1st April 2013) - Zhu, P; Chen, Y; Wang, L Y; Hong, D; Zhou, J Z; Qian, G R; Zhou, M
<x xml:space="preserve">Abstract</x> To solve the disposal problems of mining tailings and calcium fluoride sludge (CFS), waste serpentine tailings (WSTs), waste kaolin tailings (WKTs), and CFS were tested as components for a ceramic product to be used as a building material. The ceramic properties were analyzed by thermal analyses, X-ray diffraction (XRD), morphological structure analyses, Raman spectra, compressive strength measurement, and toxicity characteristic leaching procedure (TCLP). Thermal analyses showed that the significant weight loss of the sample at 1000°C was the release of H2O and CO2 rather than HF. X-ray diffraction verified that the main crystalline phase of the ceramic was anorthite. Raman spectra indicated that fluorine in CFS substituted for oxygen to form the structure of SiOxF4−x tetrahedra. Toxicity characteristic leaching procedure and corrosion resistance tests indicated that fluorine solidified into anorthite phase did not release into solution. Therefore, converting WST, WKT, and CFS into a ceramic product is in accordance with the concept of sustainable development. Pour résoudre les problèmes d'élimination des résidus miniers et des boues de fluorure de calcium (CFS), les déchetsrésidus de serpentine (WSTs), les résidus de kaolin déchets (WKTs), et du CFS ont été testés en tant que composants pourun produit céramique pouvant être utilisé comme matériau de construction. Les propriétés céramiques ont été analysées paranalyses thermiques, diffraction des rayons X (XRD), analyses de la structure morphologique, les spectres Raman, mesure de la résistance à la compression, et par lessivage des caractéristiques toxiques (TCLP). Les analyses thermiques ont montré que la perte de poids significative de l'échantillon à 1000°C a été la libérationde H2O et CO2 plutôt que de HF. La diffraction des rayons X a vérifié que la phase cristalline principale de lacéramique était anorthite. Les spectres Raman ont indiqué que le fluor contenu dans le CFS a remplacé l'oxygène pourformer la structure de SiOxF4-x tétraèdres. Lessivage des caractéristiques toxiques et lestests de résistance à la corrosion ont indiqué que le fluor solidifié en phase anorthite ne s'est pas transformé dans lasolution. Par conséquent, la conversion de WST, WKT, et CSF en un produit céramique est en conformité avecle concept de développement durable.